Strategi Pengembangan Pembelajaran Pondok Pesantren Al Falah Somolangu Kebumen - Ngusman, Aly (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2018)
Discussion about the role of boarding schools in the formation and development of education, in particular the Islamic education, in Indonesia hardly needs to be debated and doubt. Long before Indonesia became independent, the institutions lead by the scholars (kyai) is present in the Earth. History shows that the boarding school is not only able to keep resistance from exposure to the times, but also can take care of its development which continues to increase over time. According to existing data, the institution was first established, especially in Java, in the 15th century by Maulana Malik Ibrahim (one of the oldest walisongo) and then developed by the other walisongo. At the end of the 19th century, the number of boarding school in Java developed reaches 300 boarding school, and based on the Notes Database boarding schools of ministry of religion RI, the number of boarding schools the year 2018, this amounts to about 21,321. The resistance and sustainable development of the boarding schools that certainly could not be released from the academic tradition developed which has a pretty strong distinction. One of them is the pattern of his education is transformative. It makes boarding school is not simply a religious institution that merely engaged in the world of religious education for the students, but at the same time have the concern and active role of the community in jointly empower themselves. These values also did not escape from Al-Falah boarding school Somolangu, Kebumen. It will also make boarding school can be instrumental in giving a concrete contribution for global life.